Potensi Penggunaan Sistem Modular dalam Pembinaan Rumah Mampu Milik - Zullaile, Muhammad Hanafi; Omar, Roshartini; Masrom, Mohd Asrul Nasid; Ismayatim, Norddin (Research in Management of Technology and Business, 2021)
Modular system is a modern construction system innovated from IBS, aims to overcome the limitations of IBS in the construction industry that is to improve the quality, productivity, and sustainability of a construction project. In Malaysia, the level of use of modular systems is still low because the IBS system is still not widely used in construction project. Affordable housing is one of the construction projects that are in high demand, especially from the community living in the city and suburbs. Modular systems are seen to have great potential in the construction of affordable housing due to the applied concept of modular units. However, the number of studies conducted related to this matter is still low and requires more in-depth research on this issue. Therefore, this study was conducted with the objectives to identify the suitability factors of the use of modular systems in the construction of affordable housing and to study the potential use of modular systems in the construction of affordable housing. The methodology of this study uses a qualitative method, namely interviews with 4 respondents from G6 and G7 CIDB grade contractor companies in Selangor and Johor who are involved in the field of building prefabrication. The results show that the suitability factors of modular system are project cost, technological advance, readiness of industry players and project construction duration while the potentials of modular system are design, market and economy, community quality of life and environmental well-being. In conclusion, it is hoped that this study can provide benefits to construction industry stakeholders who implement affordable modular house construction projects.